Self‐reported fatigue in children with advanced cancer: Results of the PediQUEST study. Issue 18 (6th October 2018) - Ullrich, Christina K.; Dussel, Veronica; Orellana, Liliana; Kang, Tammy I.; Rosenberg, Abby R.; Feudtner, Chris; Wolfe, Joanne
Abstract : BACKGROUND: Pediatric cancer‐related fatigue is prevalent and significantly impairs health‐related quality of life, yet its patterns and correlates are poorly understood. The objectives of this study were to describe fatigue as prospectively reported by children with advanced cancer and to identify the factors associated with fatigue and associated distress. METHODS: Children (age ≥2 years) with advanced cancer (N = 104) or their parents at 3 academic hospitals reported symptoms at most weekly over 9 months using the computer‐based Pediatric Quality of Life Evaluation of Symptoms Technology (PediQUEST) system. PediQUEST administered a modified version of the Memorial Symptom Assessment Scale (PQ‐MSAS) as part of a randomized controlled trial. Clinical information was abstracted from medical records. Primary outcomes were: 1) fatigue prevalence (yes/no response to PQ‐MSAS fatigue item) and 2) fatigue distress (composite score of severity, frequency, and bother). Multivariable models were constructed to identify factors independently associated with fatigue prevalence and scores reflecting fatigue distress (ie, burden). RESULTS: Of 920 reports, 46% (n = 425) noted fatigue. When reported, fatigue was of high frequency in 41% of respondents (n = 174), severity in 25%of respondents (n = 107), and bother in 34%of respondents (n = 143). Most reports (84%; n = 358) were associated with scores indicating fatigue distress. In multivariable analyses, fatigue was associated with older age, lower hemoglobin, and distress from particular symptoms (anorexia, nausea, sleep disturbance, sadness, and irritability). In contrast, fatigue distress was associated with distress from nausea, cough, and pain. CONCLUSIONS: Fatigue is common among children with advanced cancer and is often highly distressing. Interventions focused on uncontrolled symptoms may ease fatigue distress in children with advanced cancer. Abstract : Fatigue is common among children with advanced cancer and is often distressing. Although fatigue is associated with older age, lower hemoglobin, and distress from particular symptoms (anorexia, nausea, sleep disturbance, sadness, and irritability), fatigue distress is associated with distress from nausea, cough, and pain.